Biomechanical analysis of the techniques and phase ratios of domestic elite triple jumpers - Song, J.-H.; Ryu, J.-K. (International Journal of Applied Sports Sciences, 2011)
The purpose of this study was to analyze and improve the techniques of the KDH triple jumper. Both successful and failed trials of the subject who won the triple jump championship in the 63th National Athletics Championship in 2009 were included in this study. The analyzed data (final stride, hop distance, step distance, jump distance, phase ratio, location of center of gravity, velocity, and the takeoff angle) during each event were studied after filming the actual competition of the KDH jumper. Six video cameras (PD170, Sony) were used to record the performance of the jumper and they were installed as to not interrupt o the performance. The film speed was set at 30frames/sec and the shutter speed was 1/250 sec. The data were smoothed using a Butter worth second order low pass filter with a cut off frequency of 10 Hz. The following conclusions were reached by analyzing the subject`s trials. The subject used both the hop-dominated technique and the balanced technique simultaneously, and the best national record was established by using the balanced technique. To improve his record, the KDH jumper needs to reduce the loss of horizontal velocity by creating the longer takeoff distance and the shorter landing distance throughout the hop, the step, and the jump. The technique used for the stamping motion during the step phase requires further development because the KDH jumper lost 20% of his horizontal velocity during this phase. Also, the KDH jumper should decrease his takeoff angle by ~1° in the step phase and increase it by ~1° in the jump phase.